(3SdWI GdbGVj GdhWfj aj GdQbGHI Ydi GdJMcje (B/ s - (3EHQGgje eMeO GdSjO TGgjfs; (3YHO GdefYe ReRe (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3jOQS GdJfXje GdbGfhfi dSdWI GdbGVi GdhWfi ai GdQbGHI Ydi GdJMcje(B: (3GdJhajb Hjf GYJHGQjf(B: (3GdChd (B- (3Cf GdgOa GdCSGSi ef GddLhA Edi GdJMcje cBdjI dMd GdfRGYGJ jJeKd ai SQYI GdaUd ai GdfRGY(B: (3h JaGOi GddLhA Edi ELQGAGJ GdJbGVi CeGe GdeMGce GdQSejI(B: (3CeG GdGYJHGQ GdKGfi ajJeKd ai MeGjI GdfXGe GdbGfhfi h Mbhb GdZjQ(B: (3adG jecf Gdbhd HGSJbdGd GdJMcje Ydi MSGH GdfXGe GdbGfhfi h GdSeGM HJfajP cd Mce JMcje Ohf Ci ELQGA QbGHi; h MjK Cf GdGYJHGQjf dG jecf JLGgdgeG(B: (3abO CbQJ bhGfjf GdJMcje GdeNJdaI (B- (3h Ydi QCSgG GdbGfhf GdeUQi (B- (3HSdWI GdJONd GdbVGFi ai Yed GdeMcejf; cdeG GbJVJ GdMGLI Cf jJONd djbOe YhkfG heSGYOI Ch dQaY UYhHI WQCJ CeGe GdgjFI GdJMcjejI(B: (3Ch Cf jbhe HQbGHI YedjI GdJMcje(B: (3ShGA NdGd Jdc GdeQGMd(B: (3Ch HQaY OYhi HWdGf Mce GdJMcje(B: (3dcf GdQbGHI GdbVGFjI HGdeYfi Gdafi ddcdeI(B: (3Jchf Mjf ojWdH ef QFjS GdeMceI GdCeQ HJPjjd Mce GdeMcejf HGdUjZI GdJfajPjI; Ci LYd Mce GdJMcje jfJbd Edi eUGa GdCMcGe GdbVGFjI(B: (3GdLGgRI ddJfajPs
The legal regulation of the power of the national judge in the control of arbitration examines the conciliation of two considerations. First, the primary purpose of resorting to arbitration as a mechanism for resolving disputes is to expeditiously resolve disputes, avoid recourse to the official courts. The second consideration is the protection of the legal system and the rights of others; by giving the litigants legal guarantees to correct the errors of the judgments. Whereas the two considerations cannot be ignored, the various arbitration laws primarily Egyptian-law-have approved the power of judicial intervention in the work of the arbitrators; whenever necessary, intervene to provide assistance and help to elevate the difficulty facing the arbitral tribunal; Or to supervise the arbitration process, or to file a claim for invalidity of the arbitral award, but judicial control in the technical sense of the word shall be when the Head of the Court is requested to append the arbitrators' judgment in the executive form; that is, to make the arbitral award move to the judicial judgments.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2018.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B614 - 634.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdOhdj GdNGUs; (3GdQbGHI GdbVGFjI s; (3GfJgGA GJaGb GdJMcjes; (3eHOC GdGNJUGU HGdGNJUGUs; (3GdJMcjeGJ GdCLfHjIs; (3NUheI GdJMcje s; (3CMcGe GdJMcje GdCLfHjIs; (3GdJMcje GdGSJFfGajs; (3GJaGbjI fjhjhQcs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs